ORGANOLEPTIC QUALITY OF COW MILK KEFIR INCUBATED IN LIGHT GREEN COCONUT SHELLS (Cocos nucifera L. var. viridis Hassk) - K. B., GINTING; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan; Vol 25 No 2 (2022): Vol. 25 No. 2 (2022), 2022)
This research was conducted to determine the organoleptic quality of kefir incubated in light green coconut shells (Cocos nucifera L. var. viridis Hassk) with and without coconut meat, conducted from August to October 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The experimental design used in this study was a completely randomized design (CRD) with three tre- atments and five replications. The three treatments were: P0 used a jar (control), P1 used light green coconut shell (Cocos nucifera L. var. viridis Hassk) without coconut meat, P2 uses light green coconut shell (Cocos nucifera L. var. viridis Hassk) with coconut meat. The variables observed: color, taste, aroma, texture and overall acceptance. The results of the organoleptic test were analyzed using the Kruskal Wallis test, if there was a significant differen- ce (P <0.05) followed by the Mann-Whitney test. The results showed that the organoleptic quality of cow’s milk kefir incubated in light green coconut shells (Cocos nucifera L. var. viridis Hassk) was not significantly different (P>0.05) in all treatments (P0, P1, P2). The conclusion from the results of this study shows that, incubated cow’s milk kefir in light green coconut shell (Cocos nucifera L. var. viridis Hassk) with and without coconut meat did not affect the organoleptic quality of kefir but panelists gave a response that led to preference.